The effectiveness of talent management strategies in the development of human resources teaching from the point of view of the leaders and members of the faculty of Taibah University - Al-Skran, Badrya Abdullah (Journal of Educational and Psychological Sciences, 2019)
The study aimed to identify the effectiveness of talent management strategies in human resource development at the University of Taibah, And to develop the necessary scientific solutions and recommendations, which can contribute to enhancing the effectiveness of talent management strategies in human resource development. Using the descriptive approach, study sample consisted of 67 leader, the leader of the 95 representing the entire community of the original study, and88member of the faculty members out of 365. The study relied on questionnaire tool, included thirty-eight parts, distributed over four axes, polarization, the discovery, the professional development, and the retention. In addition to an open question.The study found a range of results, which are;The general grade of the effectiveness of talent management strategies in human resources development at the University of Taibah from the perspective of leaders and members of the faculty average, is a mean 3.13.The polarization strategy is the most effective in the talent management in the development of human resources at the University of Taibah, a mean 3.35. The second was professional development with an average (3.17) and third discovery with an average of (3.09) The retention strategy came to be the least strategy in the talent management effectiveness in human resource development at the University of Taibah, a mean 2.93.In light of the results , a number of recommendations and suggestions.
Keywords: talent management strategies; human resource development; Taibah University